Aplikasi Ekstrak Daun Binahong (Anredera cordifolia (Ten) Steenis) dalam Air Minum terhadap Kualitas Karkas Ayam Jawa Super - T Affandi; A A Candra; N Irwani (PETERPAN (Jurnal Peternakan Terapan), 2021)
This research aims to identify how much the benefits of binahong leaf extract as a feed additive to the quality of super java chicken carcasses. This research was conducted in the Cage and Laboratory of Lampung State Polytechnic Livestock Department. The material used in this study was 100 super Java chicken day old chick (DOC) that was placed in a stage cage with a size of 100 cm x 100 cm and a height of 60 cm per plot. The research design used a complete random design with 5 treatments and 3 replays. P1: without treatment; P2: binahong leaf extract 250 mg/kg body weight; P3: binahong leaf extract 500 mg/kg body weight; P4: binahong leaf extract 750 mg/kg body weight and P5: binahong leaf extract 1.000 mg/kg body weight. The results of the variety analysis showed that the use of binahong leaf extract on carcass quality had affect (P>0.05) on the life weight and weight of carcasses, but did not affect the percentage of carcasses, the percentage of cooking shrink and the pH of meat, doses 1.000 mg/kg of body weight showed the best results on live weight and carcass weight of the super java chicken.